2012
DOI: 10.1039/c2jm14718a
|View full text |Cite
|
Sign up to set email alerts
|

The preparation of functionalized graphene oxide for targeted intracellular delivery of siRNA

Abstract: Functionalized graphene oxide (GO) for the targeted intracellular delivery of hTERT siRNA was prepared by conjugating GO with polyethylene glycol (PEG) and folic acid, followed by the loading of siRNA with the aid of 1-pyrenemethylamine hydrochloride via p-p stacking. It was found that it could target the HeLa in vitro and the transfected hTERT siRNA could knockdown the protein expression level and mRNA level efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(53 citation statements)
references
References 27 publications
1
51
0
1
Order By: Relevance
“…L. Zhang et al [163] prepared amide derivative of GO with polyethyleniminom in order to load small interfering RNA and doxorubicin. X. Yang et al [215] revealed similar results with polyethylene glycol and 1-pyrenemethylamine-functionalized GO. After further conjugation with folic acid, the complexes were able to selectively deliver small interfering RNA to cells and could effectively knockdown the targeted gene.…”
Section: Gene Delivery By Nanographenesupporting
confidence: 63%
See 1 more Smart Citation
“…L. Zhang et al [163] prepared amide derivative of GO with polyethyleniminom in order to load small interfering RNA and doxorubicin. X. Yang et al [215] revealed similar results with polyethylene glycol and 1-pyrenemethylamine-functionalized GO. After further conjugation with folic acid, the complexes were able to selectively deliver small interfering RNA to cells and could effectively knockdown the targeted gene.…”
Section: Gene Delivery By Nanographenesupporting
confidence: 63%
“…By derivatization of carboxylic groups on GO with polyethylenimine, chitosan or 1-pyrenemethylamine, amidic bonds were established [214,162] that allow electrostatic [188] or non-polar π-π stacking interactions [215] and show effi cacy with plasmid DNA or small interfering RNA delivery. Functionalized GO could have effective delivery of molecular beacons [216] and aptamers [217] to cells for in situ specifi c molecule detection.…”
Section: Gene Delivery By Nanographenementioning
confidence: 99%
“…16 However, applications of graphene in the fields of bioimaging and optoelectronics are limited because graphene is a zero-bandgap semiconductor. 7, 8 In order to generate the bandgap in graphenes, a zero-dimensional derivative, graphene quantum dots (GQDs) have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Sequential delivery of Bcl-2 siRNA and doxorubicin into cancer cells by the GO-PEI conjugate showed signifi cantly improved cell killing effi cacy via a synergistic effect. Yang and co-workers [ 140 ] prepared functionalized GO for the targeted intracellular delivery of hTERT siRNA by conjugating GO with PEG and FA. It could target the HeLa in vitro and the transfected hTERT siRNA could knockdown the protein expression level and mRNA level effi ciently.…”
Section: Image Agentsmentioning
confidence: 99%